PENGARUH TRANSAKSI PIHAK BERELASI, LEVERAGE, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK DENGAN MANAJEMEN LABA SEBAGAI VARIABEL MODERASI - Carine; Carine, Carine; J.Arsjah, Regina (Universitas Katolik Indonesia Atma Jaya, 2025)
This study purposes to examine related party transactions, leverage, firm size, as well as profitability on tax avoidance effect, with earnings management as a moderating variable. Sample of this study comprises 30 industries in the non-cyclical consumer sector listed on the Indonesia Stock Exchange (IDX) in 2020-2023, selected through purposive sampling, resulting in 120 observations. Secondary data were gained from financial statements and annual reports. Data were analyzed using multiple linear regression via the EViews 9 application. The results indicate that leverage has a significant positive effect on tax avoidance, while related party transactions, firm size, as well as profitability show no significant influence. Additionally, earnings management moderates the relationship between firm size as well as tax avoidance but does not moderate the relationships among the other independent variables and tax avoidance. These findings suggest that earnings management is not actively used as a tool for tax avoidance strategies in this sector.